Integrated metabolite profiling and transcriptome analysis unraveling mechanism of RC catabolism in Paenarthrobacter ilicis CR5301 - Li, Hongfei; Sun, Daqing; Cao, Longkui; Wang, Baohui (Frontiers in Microbiology, 2023)
Steviol glycosides are ideal sweeteners that are widely used in food, medicine, and cosmetics. Rebaudioside C (RC) is considered to be the third most abundant steviol glycoside, which has a bitter aftertaste that limits its application. Hydrolysis of RC to generate other bioactive steviol glycosides is an effective way to promote its additional utilization. In our previous study, a bacterium Paenarthrobacter ilicis CR5301 was isolated and identified for hydrolyzing RC with high efficiency. Herein, the expression profiles of P. ilicis CR5301 in the deletion and presence of RC were investigated by RNA-seq. The RC metabolites were identified by high-performance liquid chromatography and ultra-performance liquid chromatography-triple-time of flight mass spectrometry. Novel results were discovered in four aspects of research. First, the identification of metabolites revealed that four metabolites, namely, dulcoside A, dulcoside B, dulcoside A1, and steviol, were produced during RC metabolism. Second, RNA-seq analyses unraveled that 105 genes of P. ilicis CR5301 were significantly differentially expressed, and 7 pathways were significantly enriched. Third, independent RT-qPCR verified the accuracy and reliability of the RNA-seq results. Finally, a complete catabolic model of RC in P. ilicis CR5301 was proposed, and key genes were indicated in the RC catabolic metabolism by combining them with literature and sequence alignments. This study comprehensively unraveled the genes and pathways of RC catabolism in P. ilicis CR5301 at the transcriptional and metabolic levels. It provided new insights and evidence for understanding the mechanism of RC catabolism in bacteria. Key candidate genes may potentially contribute to the RC hydrolysis and preparation of other functional steviol glycosides in the future.